EFFECT OF PHOTOPERIOD AND MELATONIN ON SPLENOCYTE PROLIFERATION IN FRESHWATER SNAKE, NATRIX PISCATOR - MANISH KUMAR TRIPATHI; RAMESH SINGH (The Bioscan, 2012)
The purpose of the present experiment was to investigate the effect of different photoperiod regimens on splenocytes proliferation in fresh-water snake Natrix piscator. To study the effect of photoperiod on lymphocyte activities, different photoperiod regimens were used. These were: constant light (24D) and dark (24L) for 30 days. Animals kept under natural day length served as control. Splenocyte proliferation was studied colorimetrically using MTT 3-(4, 5-dimethylthiozol-2-yl)-2, 5 diphenyl tetrazolium bromide]. Mitogens used were T-cell mitogen, concanavalin A (ConA; 5 and 10μg mL-1) and phytohemagglutinin (PHA; 5 and 10μg mL-1). The direct effect of melatonin on immune cells was evaluated by adding melatonin to the cultures obtained from animals kept in different photoperiod conditions. The results of these studies suggest that splenic lymphocytes from 24D animals have increased mitogen-induced proliferative response, while those from 24L animals have decreased Proliferative response. Further, in vitro melatonin caused significant enhancement of proliferation of splenocytes obtained from 24L treated animals. Our results emphasize the effect of photoperiod and melatonin on proliferative activity of splenocytes in this species.